Pharmacological Inhibition of Core Regulatory Circuitry Liquid–liquid Phase Separation Suppresses Metastasis and Chemoresistance in Osteosarcoma. Issue 20 (25th August 2021) - Lu, Bing; Zou, Changye; Yang, Meiling; He, Yangyang; He, Jincan; Zhang, Chuanxia; Chen, Siyun; Yu, Jiaming; Liu, Kilia Yun; Cao, Qi; Zhao, Wei
Abstract: Liquid–liquid phase‐separated (LLPS) transcriptional factor assemblies at super‐enhancers (SEs) provide a conceptual framework for underlying transcriptional control in mammal cells. However, the mechanistic understanding of LLPS in aberrant transcription driven by dysregulation of SEs in human malignancies is still elusive. By integrating SE profiling and core regulatory circuitry (CRC) calling algorithm, the CRC of metastatic and chemo‐resistant osteosarcoma is delineated. CRC components, HOXB8 and FOSL1, produce dense and dynamic phase‐separated droplets in vitro and liquid‐like puncta in cell nuclei. Disruption of CRC phase separation decreases the chromatin accessibility in SE regions and inhibits the release of RNA polymerase II from the promoter of SE‐driven genes. Importantly, absence of CRC key component causes a reduction in osteosarcoma tumor growth and metastasis. Moreover, it is shown that CRC condensates can be specifically attenuated by the H3K27 demethylase inhibitor, GSK‐J4. Pharmacological inhibition of the CRC phase separation results in metastasis suppression and re‐sensitivity to chemotherapy drugs in patient‐derived xenograft model. Taken together, this study reveals a previously unknown mechanism that CRC factors formed LLPS condensates, and provides a phase separation‐based pharmacological strategy to target undruggable CRC components for the treatment of metastatic and chemo‐resistant osteosarcoma. Abstract : Core regulatory circuitry (CRC) factors forms liquid–liquid phase‐separated condensates at super‐enhancers to regulate chromatin accessibility and oncogenic transcription. Pharmacological inhibition of the CRC phase separation by GSK‐J4 suppresses metastasis and chemoresistance in osteosarcoma patient‐derived xenograft model.